Carotid artery screening at the time of coronary artery bypass - Does it influence neurological outcomes?. (15th September 2017) - Narayan, P.; Khan, Md. W.; Das, D.; Guha Biswas, R.; Das, M.; Rupert, E.
Abstract: Objective: Patients undergoing coronary artery bypass graft (CABG) are recommended to undergo carotid duplex study in presence of risk factors. Aim of the study was to quantify the relationship between risk factors and presence of carotid disease and examine if screening influenced outcomes. Methods: Over a four year period in a single institution, 4364 consecutive patients presenting for primary isolated CABG were enrolled to undergo carotid duplex scanning. Patients were grouped as no significant carotid artery stenosis (< 50%), moderate stenosis (50%–70%) and severe stenosis (> 70%). Sub group analysis of patients with severe carotid stenosis was performed. Sensitivity of risk factors thought to be associated with carotid disease was also assessed. Results: Of the 4364 patients, 406 patients (9.3%) had moderate or severe carotid artery stenosis. 32 (7.88%) had bilateral disease. Age > 65, hypertension, left main stem stenosis, peripheral vascular disease, and previous neurological injury were all associated with carotid artery disease (p < 0. 01). Diabetes (p = 0.06) and smoking (p = 0.79) were not significant risk factors. In patients with moderate carotid artery stenosis there was no difference in the incidence of major 4 (0.98%) vs.18 (0.45%) p = 0.14 or minor 8 (1.9%) vs. 56 (1.41%); p = 0.38 neurological outcomes. However, severe carotid stenosis was associated with an increase in all-cause mortality but no increase in neurological events. Conclusions: In the presence of risk factors carotid screening identifies at risk population. Severe carotid stenosis was associated with increased all-cause mortality. However, moderate stenosis did not influence neurological outcomes or mortality in patients undergoing coronary artery bypass grafting.